1989
DOI: 10.1016/0014-5793(89)81092-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of protein kinase C by casein kinase‐1

Abstract: Because phosphorylation of protein kinase C (PKC) may provide a mechanism for regulation of this enzyme, we have examined the ability of two other kinases to phosphorylate PKC. Our results show that casein kinase 1 (CK‐1), but not casein kinase 2 (CK‐2), can phosphorylate PKC in the absence of Ca2+ and phospholipids. The 32P incorporation into PKC in the presence of Ca2+ and phospholipids is also enhanced by CK‐1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Other known protein kinases which phosphorylate PKC isoforms include casein kinase-1 (CK1) and casein kinase-2 (CK2). Rat brain PKC was shown to be phosphorylated by CK1 (Vila et al, 1989). Another report demonstrated that PKCβ was phosphorylated by rat lung CK2 and that neither PKCγ nor PKCα was significantly phosphorylated by the same kinase (Tominaga et al, 1991).…”
Section: Pkc Kinasesmentioning
confidence: 98%
“…Other known protein kinases which phosphorylate PKC isoforms include casein kinase-1 (CK1) and casein kinase-2 (CK2). Rat brain PKC was shown to be phosphorylated by CK1 (Vila et al, 1989). Another report demonstrated that PKCβ was phosphorylated by rat lung CK2 and that neither PKCγ nor PKCα was significantly phosphorylated by the same kinase (Tominaga et al, 1991).…”
Section: Pkc Kinasesmentioning
confidence: 98%